Potential limits to anthropogenic mortality of small cetaceans in coastal waters of British Columbia - Williams, Rob; Hall, Anna; Winship, Arliss (Canadian Journal of Fisheries and Aquatic Sciences, 2008)
Small cetaceans are by-caught in salmon gillnet fisheries in British Columbia (BC) waters. In Canada, there is currently no generic calculation to identify when management action is necessary to reduce cetacean bycatch below sustainable limits. We estimated potential anthropogenic mortality limits for harbour (Phocoena phocoena) and Dall's (Phocoenoides dalli) porpoises and Pacific white-sided dolphins (Lagenorhynchus obliquidens) using quantitative objectives from two well-established frameworks for conservation and management (the United States' Marine Mammal Protection Act and the Agreement on the Conservation of Small Cetaceans of the Baltic and North Seas), which are similar to some management objectives developed from marine mammal stocks elseswhere in Canada. Limits were calculated as functions of (i) a minimum abundance estimate (2004-2005); (ii) maximum rate of population increase; and (iii) uncertainty factors to account for bias in abundance estimates and uncertainty in mortality estimates. Best estimates of bycatch mortality in 2004 and 2005 exceeded only the most precautionary limits and only for porpoise species. Future research priority should be given to determining small cetacean stock structure in BC and refining species-specific entanglement rates in these and other fisheries. The approach offers a quantitative framework for Canada to meet its stated objectives to maintain favourable conservation status of cetacean populations.